Synthesis and characterization of Cu/ZnO catalyst on carbon nanotubes and Al2O3 supports - Mohd Zabidi, N.A. (Trans Tech Publications Ltd, 2018)
CO2 conversion into valuable chemicals is an attractive option to deal with the increasing CO2 concentration in the atmosphere. In this study, Cu/ZnO catalyst was synthesized on multi-walled carbon nanotubes (MWCNTs) and Al2O3 supports via incipient wetness impregnation method. The physicochemical properties of the catalysts were investigated using TEM, XRD, N2 adsorption-desorption analysis, H2-TPR and XPS. The performance of the synthesized catalysts in a CO2 hydrogenation reaction was evaluated in a fixed-bed reactor at 503 K, 22.5 bar and H2:CO2 ratio of 3:1. TEM images showed that Cu/ZnO nanoparticles were deposited inside the CNTs as well as on the exterior walls of the CNTs. The average CuO crystallite size on Al2O3 and CNTs supports was 15.7 and 11 nm, repectively. Results of H2-TPR studies showed that the reducibility of the catalyst was improved on the CNTs support. XPS analysis confirmed the presence of Cu2+ in the samples, however, the binding energy of Cu 2p3/2 peak on the Al2O3 support was shifted to higher value compared to that of CNTs support. Products obtained from the CO2 hydrogenation reaction in the presence of these catalyts were methanol, ethanol, methyl formate and methane. The CO2 conversion of around 23 was obtained using both types of catalysts, however, Cu/ZnO on CNTs resulted in higher yield of methyl formate compared to that of Al2O3-supported catalyst. Â© 2018 Trans Tech Publications, Switzerland.